Dieting, weight perception and eating disorders in adolescence and later mental health disorders. A population-based registry study of Norwegian youth - Martinussen, Astri Sneve (UiT Norges arktiske universitet, 2018)
Background The relationship between body image and eating disorders in adolescence has been largely addressed, but less information exists about the potential longitudinal associations between dieting in adolescence and mental health problems later in young adulthood. The aim of this thesis was first to examine the association between dieting and eating disorder in adolescence and later mental health disorders in young adulthood. Secondly, we examined how sociodemographic and psychosocial factors affected this relationship. Third, we examined how BMI and weight perception was associated with later mental health problems. Sample and methods Data was obtained from the Norwegian Arctic Adolescent Health Study (2003–2005) that was linked to the Norwegian Patient Registry (2008–2012). In total, 3987 (68%) of all 5877 invited participants consented to the registry linkage. Dieting was measured by the participants reporting dieting behavior, including different dieting methods. Eating disorders in adolescence was measured by the participants that reported being treated for an eating disorder. BMI was calculated based on self-reported weight and height. Bivariate analyses were carried out using Chi-square tests, one-way ANOVA and logistic regression for the examination of cross-sectional and longitudinal data. Results Significantly more females reported to have tried dieting compared to males. Mental healthcare users, and the participants registered with an eating disorder and personality disorder in young adulthood, reported highest percentages of dieting in adolescence. Dieting in adolescence was also associated with mood disorders and anxiety disorders in young adulthood. We found no significant association between dieting in adolescence and later mental health disorders when adjusted for adolescent sociodemographic and psychosocial factors. Conclusion Dieting in adolescence is highly prevalent and associated with several mental health disorders in young adulthood, not only with eating disorders. Even though our ...